PENGEMBANGAN LKPD INTERAKTIF BERBASIS INKUIRI TERBIMBING PADA MATERI PERSAMAAN REAKSI UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Mokoginta, Meliyani; Saiya, Abdon; Anom, I. D. K (LPPM Politeknik Saint Paul Sorong, 2025)
Effective learning requires an active, creative and fun approach, and provides space for students to channel their potential according to their interests and talents. In the context of chemistry education, which involves abstract concepts such as changes in matter at the atomic or molecular level, learning strategies are needed that support in-depth understanding. One relevant approach is the guided inquiry model, which provides direction to students to develop their analytical skills. This research aims to develop an interactive Student Worksheet (LKPD) based on guided inquiry on chemical reaction equations to improve the learning outcomes of class X SMA Negeri 1 Bolaang. Development was carried out using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model with validation by material and media experts, as well as product trials. Data collected includes product feasibility validation, student learning outcomes, and input from validators. The research results show that guided inquiry-based LKPD is valid, practical and effective for use as a learning medium. This product helps students not only understand concepts but also carry out scientific proofs, thereby improving critical thinking skills. The benefits of this research include contributions for students, teachers and researchers in developing innovative and interactive learning media in the field of chemistry education.